Les Usages dans les programmes d’expérimentation sur le logement mis en œuvre par le Plan Construction et le PUCA (1971-2021) - Francesco Bogoni (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The role of usages in the reflection on housing quality is studied in the housing experimentation programmes implemented by Plan Construction and PUCA since the beginning of the years 1970s. This article shows the transformations of the reflections on usages, initially approached in relation to architectural design, then to other emerging issues up to the most recent environmental concerns. These developments follow cycles of reflection. They can be explained by organizational changes in the housing production, the structure of the stakeholders’ milieu and the difficulty of going beyond the experimental framework.